Label-free Identification of Nonelectrogenic Cancer Cells using Adhesion Noise - Ell, Maximilian; Zeitler, Ralf; Thewes, Roland; Zeck, Gunther (2023 IEEE BioSensors Conference (BioSensors), 2023)
Time-continuous detection of cells on substrates without the need of optical microscopic imaging is of broad interest in biotechnological applications. We present a method how to detect cancer cells using voltage noise caused by cell adhesion which is recorded by high-density CMOS-based microelectrode arrays. We analyze our data in terms of spectral power density for two different types of arrays, each of them being optimized in a different working regime.